Perancangan Content Management System Bank Perkreditan Rakyat - Hidayat, Rachmad; Jauhari, Achmad (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
Objectives expected of this research is to design a CMS information system for rural banks (BPR). This study uses primary data and secondary data. Data collection method used is the in-depth interviews with management and direct observation processes that occur in BPR. CMS development easier for the BPR to provide the latest information to its customers, making it easier marketing. Testing the success of the CMS system show that the quality of the CMS system is determined by the design layout of the interface and the required forms is well defined. Quality of information is determined by the ease of CMS, understood by users and customers. A lot of quality process is determined by the quality of information produced CMS. Analysis of costs and benefits of the CMS information system stated that the CMS information system project feasible and able to provide benefits to the BPR.